2022
DOI: 10.1038/s41598-022-13675-3
|View full text |Cite
|
Sign up to set email alerts
|

Trusting COVID-19 vaccines as individual and social goal

Abstract: Trust in vaccines and in the institutions responsible for their management is a key asset in the global response to the COVID-19 pandemic. By means of a structured multi-scales survey based on the socio-cognitive model of trust, this study investigates the interplay of institutional trust, confidence in COVID-19 vaccines, information habits, personal motivations, and background beliefs on the pandemic in determining willingness to vaccinate in a sample of Italian respondents (N = 4096). We observe substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
(57 reference statements)
2
14
0
1
Order By: Relevance
“…However, only views of vaccines as a collective choice to protect others accounted for variance in willingness to receive a COVID‐19 vaccine, over and above the effects of sociodemographic characteristics. This finding replicates existing work showing that viewing vaccines as prosocial, but not self‐protective, is associated with increased willingness to receive a COVID‐19 vaccine (Falcone et al., 2022). Individuals may not expect to be personally impacted by contracting COVID‐19, yet are willing to receive a vaccine due to concern for others at higher risk; indeed, other work has found that greater perceived risk to others, but not to self, was associated with increased intentions to vaccinate (Sherman et al., 2021).…”
Section: Discussionsupporting
confidence: 88%
“…However, only views of vaccines as a collective choice to protect others accounted for variance in willingness to receive a COVID‐19 vaccine, over and above the effects of sociodemographic characteristics. This finding replicates existing work showing that viewing vaccines as prosocial, but not self‐protective, is associated with increased willingness to receive a COVID‐19 vaccine (Falcone et al., 2022). Individuals may not expect to be personally impacted by contracting COVID‐19, yet are willing to receive a vaccine due to concern for others at higher risk; indeed, other work has found that greater perceived risk to others, but not to self, was associated with increased intentions to vaccinate (Sherman et al., 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, the pandemic brought to light the interdependencies between people and countries, hence people have become more aware that the achievement of their personal goals depends, now more than ever, on the choices made by other society members. 62 However, as reported in another study, the correlation between vaccine acceptance and psychological distress should not be exploited to promote vaccine acceptance by stoking fears, stress, and anxiety in the general population. 38 Rather, it is likely that the extremely and highly affected subgroups are more sensitive to community issues, while less affected people may be characterized by a more self-centered attitude and perception of the consequences of the pandemic.…”
Section: Discussionmentioning
confidence: 94%
“…These results, are in line with literature reporting that trust in information, in informative sources and in institution is a crucial mediator in determining willingness to accept vaccine. 62–65 Mistrust of official information may be indicative of a conspiracy mind-set perceiving evidence that vaccines are helpful as misleading and covering up evidence that vaccines are harmful. 65 Conspiracy theories and mistrust have greater appeal on younger-age and low-income population as also demonstrated by others.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic provided unusual circumstances in which we can test hypotheses about such changes. First, since COVID-19 vaccines were a new treatment for everyone, the uncertainty surrounding the related effects and side effects was higher [3], provided that higher expected probabilities of side effects of COVID-19 vaccines would discourage vaccination [4,5,6,7,8,9,8,10,11,12,13,14]. Second, a substantial subset of recipients experienced delayed localized hypersensitivity reactions to COVID-19 vaccines [15,16]; such reactions, collectively referred to as "COVID arm" have been objectively observed.…”
Section: Introductionmentioning
confidence: 99%